Uji Efektivitas Ekstrak Etanol 96% Kulit Jeruk Manis Asal Soe (Citrus sinensis L.) Sebagai Biolarvasida - Kuntum Ekawati Nurdin; Loisa Ratna Yuvita Olla; Stefany Febiand Feoh; Anita Dwi Putri Galla; Khusnul Dwi Istnaini; Elisabeth Patricia Febriani Jonison; Norma Tiku Kambuno (Research and Community Service Unit, Politeknik Kesehatan Kemenkes Kupang, 2019)
One of the plants that can be used as larvicides is sweet orange (Citrus sinensis). Sweet orange rind containing saponins, tannins, flavonoids, and triterpenoids have a characteristic of aromatic odor and bitter taste which contain 96% essential oils containing limonene, glucoside, hesperidium, and resin that can function as biolarvasides. The Regency of the Middle East South is one of the areas in Indonesia which is known as the center of sweet orange. Soe sweet orange fruit has a distinctive color, aroma, and taste compared to other oranges in Indonesia. The objectives of this study are to discover the effectiveness of the orange rind extract in killing the Aedes aegypti larvae and to identify the minimum concentration of the extract of the sweet, dry rind in killing the larvae. This type of research is experimental post-test only control group design. This research was conducted at the Health Analyst laboratory of Kupang Poltekkes (Health Polytechnic) in January 2019. The third (III) instar larvae were placed in 5 vials, each containing 15 larvae. The total number of samples needed was 375 larvae. It was mixed with 15 ml of Soe sweet orange rind with a concentration of 0.075%, 0.1%, 0.25%, 0.50%, 0.75%. One-Way Anova test results obtained sig p-value=0,000 (p<0.05), meaning that there is an influence of sweet orange rind ethanol extract on the death of larvae or orange rind extract is effective as a natural insecticide. Significant values ​​were obtained for all concentrations p=0.008 (p> 0.05) meaning that there was an average difference of each concentration. The conclusion of the study shows that the ethanol extract of sweet orange rind (Citrus sinensis L.) is effective in killing Aedes aegypti mosquito larvae with a minimum concentration of ethanol extract sweet orange rind (Citrus sinensis L.) which can kill 0.075% of larvae.